KONTRIBUSI BUDAYA POLITIK LOKAL DALAM DEMOKRATISASI (Kajian Budaya Politik dan Demokrasi Lokal Pascareformasi di Kecamatan Banyumanik Kota Semarang) - YUWANTO DAN ARIF, YUWANTO DAN ARIF (Politika: Jurnal Ilmu Politik, 2011)
AbstractThe Reformasi (Reform) of 1998 led to changes in Indonesia's various governmentalinstitutions, reforms upon the structures of the judiciary, legislature, and executive office. All thosechanges aspects of national politics affected public orientations and political activity. In the light ofpolitical culture, this study is aiming to know how the national politics changes on procedural level ofdemocratization after Reformasi influence the substantial changing of local political culture. Thisstudy employs a descriptive-qualitative method, and designated Banyumanik Subdistrict in SemarangMunicipal as a research site. This study conluded that the changing of national politics on procedurallevel of democratization are dosen’t influence the substantial changing of local political cultureKeywords: politial culture, democratization, local democracy